Modelling edge effects of mature forest plantations on peatland waders informs landscape‐scale conservation. Issue 1 (15th October 2013) - Wilson, Jeremy D.; Anderson, Russell; Bailey, Sallie; Chetcuti, Jordan; Cowie, Neil R.; Hancock, Mark H.; Quine, Christopher P.; Russell, Norrie; Stephen, Leigh; Thompson, Des B. A.; Elphick, Chris
Summary Edge effects of native forest fragmentation have been well studied, but there are few studies of open‐ground habitats fragmented by plantation forests. We measure forestry edge effects on open‐ground breeding birds, following one of Europe's biggest and most controversial land‐use transformations. The 'Flow Country' of northern Scotland is one of the world's greatest expanses of blanket bog. It became fragmented by conifer forests planted in the late 20th century, and these now adjoin open peatlands protected under European conservation legislation. Detrimental edge effects on breeding birds were anticipated, but not apparent shortly after planting. Using survey data collected in 2003–2006, and logistic regression modelling, we tested whether breeding distributions of three wader species of international conservation concern, dunlin, European golden plover and common greenshank, were influenced by distance to forest edge, controlling for habitat and topography. All three species were more likely to occupy flatter, more exposed ground close to bog pools and were influenced by peatland vegetation structure. There was an additive and adverse effect of proximity to forest edge for dunlin and European golden plover, but not common greenshank. This effect was strongest within 700 m of forest edges. We used these results to predict which areas should benefit most from removal of adjacent forestry and so guide maintenance and restoration of the bird interests of the protected areas. Synthesis and applications. Edge effects of mature forestry on dunlin and golden plover are apparent over several hundred metres and are now being used to guide forest planning in northern Scotland. The scale of edge effect is broadly consistent with other avian studies in open‐ground habitats across Eurasia and North America, so buffer zones of this order are consistent with possible impacts of plantation forestry on open‐ground habitats of bird conservation interest. Given renewed interest in conifer afforestation as a climate change mitigation measure, an improved understanding of edge effects and the mechanisms through which they operate is vital to managing plantation forestry in ways that maintain open‐ground landscapes of high conservation value.